Livestock production and sustainable agricultural Development in semi-arid West Africa - Williams, Timothy O.; Hiernaux, Pierre H.Y.; Fernández Rivera, S.; Turner, M. (OAU/STRC, 1997)
Mixed farming systems, combining crop and livestock activities, hold considerable promise for improved agricultural productivity and environmental conservation in semi-arid West Africa. Increasing population pressure and climatic changes have combined to render long-fallow periods less feasible and effective. Transhumant pastoralism, a productive and historically important pattern of livestock production in the Sahel, is under severe stress due to periodic droughts and extension of cropped lands into range-lands. This paper examines alternative options through which the integration of livestock and crop production could contribute to an intensification of agricultural production and enhance the maintenance of soil fertility in semi-arid West Africa. It reviews several aspects of livestock production focusing on social, economic and technical constraints to pastoral production and to efficient integration of crop and livestock activities. The impact of livestock on the agro-ecosystem is discussed in respect of trampling, spatial redistribution of nutrients and the biological effects of grazing and browsing on the vegetation. Technologies and economic incentives that could improve the contribution of livestock to agricultural production in semi-arid West Africa are identified. The paper demonstrates the necessity of multidisciplinary approach and of active farmer involvement in identifying, designing, and developing appropriate technologies for mixed farming systems in Africa.